Pattern and Frequency of Skin Malignancies at Laboratory of Pathology Anatomy Dr. Kariadi General Hospital in 2008-2009 - Susilorini, Susilorini; Sadhana, Udadi; Widjaya, Indra (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: A periodical database is important including for skin cancer. Periodical registration is needed to acknowledge changes in pattern and frequencies of skin lesion. Objective: The purpose of this study was to describe the pattern and the frequency of skin lesion in RSUD Kariadi.Method: A cross-sectional study was conducted through analysis of the medical records of patients diagnosed skin lesion in the pathology labolatory of RSUD Kariadi between 2008 and 2009. The variables were secondary data including age, gender, specimen area, dan histopathology diagnosis. Data was choosen by consecutive sampling from 381 medical records of skin tissues examined at laboratorium of pathology anatomy of Dr. Kariadi general hospital during 2008-2009.Result: 381 cases were recorded comprising of 246 (65%) neoplastic and 135 (35%) non neoplastic lesion. 120 patients presented with skin cancer, and 126 with benign skin lesion. Most malignancy was observed among female patients (62.5%) on age catagory of 15-39 (65%). The most common lesion was basal cell carcinoma (48.3%) followed by squamous cell carcinoma (33.3%), malignant melanoma (10%), skin appendix carcinoma (2.5%), other malignancies (4.9%).Conclusion: the most common malignancies in Dr. Kariadi general hospital before 2008 was similar to data from 13 laboratory of pathology anatomy in Indonesia, which is squamous cell carcinoma.